ETIKA PEMASARAN DIGITAL DALAM PERSPEKTIF AL-QUR’AN: ANALISIS TAFSIR TEMATIK TERHADAP PRINSIP JUAL BELI ISLAMI - Ismaila Tompo; Achmad Abubakar; Sohrah Sohrah (Universitas Ichsan Sidenreng Rappang, 2026)
The development of the contemporary digital marketing ecosystem has intensified practices of information distortion, product hyperrepresentation, visual engineering of consumption, and exploitative persuasion that increasingly diverge from the principles of honesty and transparency. This condition has not only triggered a crisis of consumer trust, but has also blurred the boundary between marketing communication and perceptual manipulation in modern business practices. Meanwhile, studies on commercial transactions in Islam have largely focused on jurisprudential aspects and normative business ethics, while the transformation of digital marketing ethics has rarely been examined through thematic Qur’anic interpretation. This study aims to reinterpret marketing ethics from the perspective of the Qur’an through a thematic tafsir (tafsīr maudhu‘i) approach toward verses concerning trade, honesty, trustworthiness, and the prohibition of deception. This research employs a qualitative library-based method with descriptive and content analysis approaches. The findings reveal that the Qur’an not only legitimizes commercial activities, but also establishes an ethical marketing foundation based on ṣidq (truthfulness), amanah (trustworthiness), justice (‘adl), and transparency as pillars of sustainable economic relations. The study further indicates that the concept of tathfif has expanded within the digital sphere into forms of non-material value distortion through the obscuring of product realities and the construction of consumer perceptions. This research proposes the concept of Qur’anic trust-based marketing as an ethical paradigm centered on trust, moral integrity, and social responsibility within contemporary digital marketing culture.